Clinical Outcomes and Complications Following Surgical Management of Traumatic Posterior Sternoclavicular Joint Dislocations: A Systematic Review. Issue 11 (November 2018) - Kendal, Joseph K.; Thomas, Katie; Lo, Ian K.Y.; Bois, Aaron J.
Abstract : Background: Traumatic posterior sternoclavicular joint dislocations are rare orthopaedic emergencies. Treatment typically consists of closed reduction, with surgical management reserved for unstable cases. Because of the low prevalence of this condition, limited clinical evidence exists for a superior surgical stabilization technique. Methods: A systematic review of the literature following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was performed. MEDLINE and Embase databases were searched using a comprehensive search strategy. A descriptive and critical analysis of the results was performed. Results: Forty relevant studies (108 cases) were identified. Favorable subjective and objective outcomes were reported for all 5 categories of stabilization described. The overall complication rate was 16%, including 4 cases of recurrent instability. Ligament reconstruction using tendon graft had the lowest recurrent instability and complication rates, and open reduction and internal fixation techniques required a second operation for implant removal in 80% of cases. Conclusions: A comprehensive review of the surgical management of traumatic posterior sternoclavicular joint dislocations is presented. Results suggest favorable outcomes for all of the methods of stabilization, with a modest complication rate. The trends observed have helped to guide the development of clinical care recommendations that aid in treatment decision-making for these injuries. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.